Avaliação de técnicas e marcadores utilizados para predizer digestibilidade e consumo por bovinos de corte mantidos em pastagem natural no contexto do modelo Pampa Corte - Silva, Aline Rodrigues (2024)
This study aimed to evaluate the impact of using digestibility values obtained by the in situ incubation technique (ISOMD) or nitrogen fecal excretion (FNOMD) on the adequacy of the Pampa Corte model for predicting average body weight gain (ADG) of free-ranging cattle. In addition, it evaluated the prediction of forage organic matter intake by beef cows on native pasture, obtained by the Pampa Corte model, comparing it to estimates obtained by conventional n-alkanes and chromium oxide methodologies. A data set of individual observations was compiled from two independent trials with growing beef cattle (12 heifers and 18 steers) on native pastures in southern Brazil, and two trials with beef cows (n=46) on native pastures in Uruguay. Body weight data, climate variables and forage attributes were used as inputs in the Pampa Corte model in experiments with growing cattle and cows, with information on gestation and lactation periods and calf data added in trials with cows. For evaluations in trials with growing cattle, feed digestibility values were obtained through in situ incubation or fecal N excretion techniques. For evaluations in studies with cows, organic matter intake was predicted by the Pampa Corte model and compared to results estimated by n-alkane and chromium oxide techniques. The observed ADG values were linearly related (P < 0,05) to those predicted by the Pampa Corte model at the individual (R2 = 0.52; RMSE = 148.9) or herd (R2 = 0.67; RMSE = 108.8) level, with no significant effect (P > 0.05) of the method to estimate digestibility. The use of FNOMD and ISOMD leads to moderate to adequate predictions (i.e., CCC ≥ 0.70 to 0.80) of ADG by the Pampa Corte model at the individual or herd level, respectively. However, the estimates present a high root mean square error of prediction (RMSE ≥ 109 g/day). In the trial with cows, the intake values estimated by the markers were not linearly related (P > 0.05) with those predicted by Pampa Corte. The average intake values estimated by the markers were higher and presented a greater amplitude than those predicted by Pampa Corte, especially during the gestation period of the cows. However, the mean intake values estimated by chromium oxide did not differ (P > 0.05) from those predicted by Pampa Corte, while those estimated by n-alkanes differed (P < 0.05). The ADG of a herd of growing cattle under pasture can be adequately predicted by the Pampa Corte model using ISOMD in the calculation of digestible cell wall content (DCW) input. However, possible errors associated with forage sampling should be considered. The limitations inherent in techniques using markers can interfere with the estimates of fecal excretion and feed intake by free-ranging ruminants. The Pampa Corte model has proven to be an important tool to aid in the production of ruminants. However, further studies are needed to evaluate the Pampa Corte for predicting intake by beef cows.